DEVELOPMENT OF INTERACTIVE MULTIMEDIA TO PREVENT MISCONCEPTIONS IN SALT HYDROLYSIS MATERIALS - Muflihatin, Laili; Sukarmin, Sukarmin (Universitas Negeri Surabaya, 2022)
This study aims to determine the feasibility of interactive multimedia that used to prevent misconceptions on salt hydrolysis material in terms of validity, practicality, and effectiveness. The type of this study is Research and Development (R&D) of the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. And this research is only limited to the implementation stage. The trial or product implementation was carried out on 20 students of high school students of eleventh grade Science. Based on the results of the research, the percentage of construct validation is 86.8% and content validation is 85.8%. Percentage of practicality based on the student response questionnaires is 86.3% and the observation questionnaires is 89%. And percentage of effectiveness obtained based on student learning outcomes is 83.4%. Thus the results of this study indicate that the interactive multimedia developed is valid, practical, and effective used to prevent students' misconceptions on the salt hydrolysis material.